The role of VNTR aggrecan gene polymorphism in the development of osteoarthritis in women - D. A. Shapovalova; A. V. Tyurin; S. S. Litvinov; E. K. Khusnutdinova; R. I. Khusainova (Вавиловский журнал генетики и селекции)
Osteoarthritis (OA) is a common multifactorial joint disease. Undifferentiated connective tissue dysplasia (uCTD) is a genetically determined lesion of the connective tissue structures, including joints, and it can be one of the factors predisposing to development of OA. Solving the problem of comorbidity of OA and uCTD signs will contribute to the early diagnosis and prophylactics of OA. Aggrecan is one of the major structural components of cartilage and it provides the ability to resist compressive loads throughout life. We examined 316 women (mean age 50.5 ± 4.77) for signs of uCTD and OA. A study of the aggrecan gene (ACAN) VNTR polymorphism, which is represented by a variable number of 57 nucleotide repeats, was performed. We searched for associations between the VNTR locus and OA in general and with an account of the localization of the pathological process, as well as with the presence of uCTD signs. Twelve allelic variants and 24 genotypes of the VNTR polymorphism of the aggrecan gene (ACAN) were identified, the most frequent variants were alleles with 27, 28 and 26 repeats. A significance of allele *27 (х2 = 6.297, p = 0.012, odds ratio (OR) = 1.50; 95 % confidence interval (CI) 1.09-2.05) in the development of OA in general, knee OA (х2 = 4.613, p = 0.031, OR = 1.52; 95 % CI 1.04-2.23), and multiple OA (х2 = 4.181, p = 0.04, OR = 1.68; 95 % CI 1.02-2.78) was revealed. Homozygous genotype *27*27 was associated with OA (х2 = 3.921, р = 0.047, OR = 1.72; 95 % CI 1-2.96), and OA with uCTD signs in women (х2 = 5.415, p = 0.019, OR = 2.34; 95 % CI 1.13-4.83).